Evaluation of a computer-based and counseling support intervention to improve HIV patients' viral loads. Issue 12 (2nd December 2018) - Marks, Gary; O'Daniels, Christine; Grossman, Cynthia; Crepaz, Nicole; Rose, Charles E.; Patel, Unnati; Stirratt, Michael J.; Gardner, Lytt I.; Cachay, Edward R.; Mathews, William C.; Drainoni, Mari-Lynn; Sullivan, Meg; et al.
ABSTRACT: We sought to integrate a brief computer and counseling support intervention into the routine practices of HIV clinics and evaluate effects on patients' viral loads. The project targeted HIV patients in care whose viral loads exceeded 1000 copies/ml at thetime of recruitment. Three HIV clinics initiated the intervention immediately, and three other HIV clinics delayed onset for 16 months and served as concurrent controls for evaluating outcomes. The intervention components included a brief computer-based intervention (CBI) focused on antiretroviral therapy adherence; health coaching from project counselors for participants whose viral loads did not improve after doing the CBI; and behavioral screening and palm cards with empowering messages available to all patients at intervention clinics regardless of viral load level. The analytic cohort included 982 patients at intervention clinics and 946 patients at control clinics. Viral loads were assessed at 270 days before recruitment, at time of recruitment, and +270 days later. Results indicated that both the control and intervention groups had significant reductions in viral load, ending with approximately the same viral level at +270 days. There was no evidence that the CBI or the targeted health coaching was responsible for the viral reduction in the intervention group. Results may stem partially from statistical regression to the mean in both groups. Also, clinical providers at control and intervention clinics may have taken action (e.g., conversations with patients, referrals to case managers, adherence counselors, mental health, substance use specialists) to help their patients reduce their viral loads. In conclusion, neither a brief computer-based nor targeted health coaching intervention reduced patients' viral loads beyond levels achieved with standard of care services available to patients at well-resourced HIV clinics.